دور التكنولوجيا الإعلام والإتصال في تفعيل الرقابة الجبائية - العائش, العرشي; حسام الدين, دروني; أسامة, الأشهب; عبدالستار, الحاج أحمد (University of eloued جامعة الوادي, 2022)
"حيث قمنا خلال هذا الفصل النظري من دراستنا، بالتعمق والتعرف على تكنولوجيا الاعلام والاتصال وكذالك الرقابة الجبائية، حيث تعرفنا في فصل دراستنا النظري بالتعرف على تكنولوجيا الاعلام والاتصال وذكر أنواعها المتوفرة والتعرف على أهم خصائصها وأهدافها بالرغم من نقص وقلة المراجع لهذا الاخير. وقد قمنا أيضا في دراستنا هذه بالوقوف على أهم عملية داخل الإدارة الضريبية وهي الرقابة الجبائية والتعريف بها وتوضيح أشكالها وأسباب قيامها وأهدافها والوسائل المتعلقة بها. كل هذا قد تم في هذا الفصل من دراستنا هذه بصفة نظرية عبر مجموعة من المراجع والكتب العلمية حول موضوع دراستنا. ""During this theoretical chapter of our study, we delved into depth and got acquainted with information and communication technology, as well as fiscal control. In our theoretical chapter, we learned about information and communication technology and mentioned its available types and identified its most important characteristics and objectives despite the lack and lack of references to the latter. In our study, we have also identified the most important process within the tax administration, which is the tax control, introducing it, clarifying its forms, the reasons for its establishment, its objectives, and the means related to it. All this has been done in this chapter of our study in a theoretical capacity through a group of references and scientific books on the subject of our study."
ماستر محاسبة
Keywords: التكنولوجيا الإعلام والإتصال. الرقابة الجبائية; Media and Communication Technology. tax control